Filosofi Larangan Bunga dalam Kontrak Syariah - Author: Nurjihad (Fakultas Hukum Universitas Islam Indonesia, 2013)
This research discusses the problems as follows: First, what main principles acting as the legal source of sharia contract law are; and, second, what the philosophical basis of the prohibition of taking interest in sharia contract law is. The method used in this research is normative juridical. The legal materials used are primary and secondary materials. The method of the research is philosophical approach. This research concludes that first, religious practice principle/basis acts as the main foundation of the legal source of the sharia contract law, and other principles act as the supporting factors to complete it. The principles of goodness and justice have ultimate position as the elaboration of religious practice principle since the values of goodness and justice are the soul and objective in all contracts made by the related parties; second, the philosophical basis of the prohibition of taking interest is subject directly to Al Qur’an. The prohibition of taking interest in sharia contract is the manifestation of the equality between the capital owners, and the consequence to take the risks and results courageously and responsibly. The prohibition agrees with the principles of goodness and justice, where there is no action of taking side at one of the related parties that are involved in a contract which means that both parties are in the equal position.